Sodium Silicate Catalyst for Synthesis Monoacylglycerol and Diacylglycerol-Rich Structured Lipids: Product Characteristic and Glycerolysis–Interesterification Kinetics - Inasanti Pandan Wangi; Supriyanto Supriyanto; Hary Sulistyo; Chusnul Hidayat (Bulletin of Chemical Reaction Engineering & Catalysis, 2022)
Sodium silicate as heterogeneous base catalysts is more environmentally friendly and easily separated by filtration. The objective of this research was to evaluate the activated sodium silicate as catalyst for synthesis of monoacylglycerol (MAG) and diacylglycerol (DAG)-rich structured lipids (SLs) from a palm olein-stearin blend. Sodium silicate was activated and functional group was characterized. Reaction was performed using 5% catalyst (w/w) at various reaction temperature (70–120 °C) for 3 h in a batch stirred tank reactor. Physical properties of SLs, such as melting point, slip melting point, and hardness of SLs were determined. Reaction kinetics were also evaluated. The results show that Si−O bending was reduced and shifted to a Si−O−Na and Si−O−Si functional groups after sodium silicate activation. Temperature had a significant effect on SLs composition at higher than 90 °C. An increase in temperature produced more MAG, resulting in better product physical properties. The best reaction condition was at 110 °C. Rate constants and the Arrhenius equation were also obtained for each reaction step. In summary, the activated sodium silicate catalyzed glycerolysis-interesterification reaction, which produced MAG and DAG at temperature higher than 90 °C. Therefore, the physical properties of SLs were improved. Copyright © 2022 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).